Respuesta :

1

 

Simplify \frac{1}{2}\imath n(x+3)​2​​1​​ın(x+3) to \frac{\imath n(x+3)}{2}​2​​ın(x+3)​​

\frac{\imath n(x+3)}{2}-\imath nx=0​2​​ın(x+3)​​−ınx=0


2

 

Add \imath nxınx to both sides

\frac{\imath n(x+3)}{2}=\imath nx​2​​ın(x+3)​​=ınx


3

 

Multiply both sides by 22

\imath n(x+3)=\imath nx\times 2ın(x+3)=ınx×2


4

 

Regroup terms

\imath n(x+3)=nx\times 2\imathın(x+3)=nx×2ı


5

 

Cancel \imathı on both sides

n(x+3)=nx\times 2n(x+3)=nx×2


6

 

Divide both sides by nn

x+3=\frac{nx\times 2}{n}x+3=​n​​nx×2​​


7

 

Subtract 33 from both sides

x=\frac{nx\times 2}{n}-3x=​n​​nx×2​​−3


ACCESS MORE